Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Pendidikan Matematika Realistik (PMRI) Pada Pokok Bahasan Luas Permukaan Bangun Ruang Sisi Lengkung - Tona Mardiyah Rambe; Febri Ananda; Ismail Hanif Batubara (Journal Mathematics Education Sigma [JMES], 2022)
Abstract. This research is a research on the development of Student Worksheets (LKPD) based on Indonesian Realistic Mathematics Education (PMRI) on the subject of curved side spaces. This study aims to 1) describe the product quality of the Student Worksheet (LKPD) based on Indonesian Realistic Mathematics Education (PMRI) on the subject of curved side space. 2) describe the results of the development of Student Worksheets (LKPD) based on Indonesian Realistic Mathematics Education (PMRI) on the subject of curved side space development. In this study, researchers used research and development procedures according to Sugiyono which have been modified. The subjects of this study were students of class IX SMP Amayatul Huda Kec. Medan, Deli Kel. Labuhan Deli. The object of this research is the Student Worksheet (LKPD) which was developed by the researcher. The data collection technique used is the result of validation and the results of interviews related to student responses regarding the use of the Student Worksheet (LKPD) product. The development procedure in this research includes: (1) Potential and problems; (2) Data collection; (3) Product design; (4) Design validation; (5) Design revision; (6) Product trial. The results of the product validation of the Student Worksheet (LKPD) developed by the researcher were 3.9 and 4.2 and included in the good category. The Student Worksheet (LKPD) developed by the researcher received a positive response from the class IX students of Amayatul Huda Middle School.Abstrak. Penelitian ini merupakan penelitian pengembangan Lembar Kerja Peserta Didik (LKPD) berbasis Pendidikan Matematika Realistik Indonesia (PMRI) pada pokok bahasan bangun ruang sisi lengkung. Penelitian ini bertujuan untuk 1)mendeskripsikan kualitas produk Lembar Kerja Peserta Didik (LKPD) berbasis Pendidikan Matematika Realistik Indonesia (PMRI) pada pokok bahasan bangun ruang sisi lengkung. 2) mendesripsikan hasil pengembangan Lembar Kerja Peserta Didik (LKPD) berbasis Pendidikan Matematika Realistik Indonesia (PMRI) pada pokok bahasan bangan ruang sisi lengkung. Dalam penelitian ini peneliti menggunakan prosedur penelitian dan pengembangan menurut sugiyono yang telah dimodifikasi. Subjek penelitian ini adalah peserta didik kelas IX SMP Amayatul Huda Kec. Medan, Deli Kel. Labuhan Deli. Objek dalam penelitian ini adalah Lembar Kerja Peserta Didik (LKPD) yang dikembangkan oleh peneliti. Teknk pengumpulan data yang digunakan adalah hasil validasidan hasil wawancara terkait tanggapan siswa mengenai penggunaan produk Lembar Kerja Peserta Didik (LKPD). Prosedur pengembangan dalam penelitian ini meliputi : (1) Potensi dan masalah; (2) Pengumpulan data; (3) Desain produk; (4) Validsi desain; (5) Revisi desain; (6) Uji coba produk. Hasil validasi produk Lembar Kerja Peserta Didik (LKPD) yang dikembangkan oleh peneliti adalah 3,9 dan 4,2 dan termasuk dalam kategori baik. Lembar Kerja Peserta Didik (LKPD) yang dikembangkan peneliti mendapat respon positif dari peserta didik kelas IX SMP Amayatul Huda.